2008
DOI: 10.1002/glia.20673
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of TNFα in hypoxic suppression of astrocyte glutamate transporters

Abstract: Transporter-mediated glutamate uptake is a principal function of astrocytes. Our previous studies have shown that this process is compromised under hypoxic conditions through the NF-kappaB mediated inhibition of expression of the glutamate transporters EAAT-1 and EAAT-2. Here, we demonstrate that identical conditions of hypoxia (1% O(2), 24 h) lead to a dramatic increase in TNFalpha production from astrocytes without altering their viability. This hypoxia-evoked production of TNFalpha was prevented in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…As shown in T cells and cardiomyocytes, inhibition of any of these components may be sufficient to severely limit transcription of target genes, although the activity of each is insufficient to direct transcription on its own (33). Interestingly, EAAT2 levels were recently shown to exhibit down-regulation in response to TNF␣ through a mechanism involving NFB (98). Note then that the CN/NFAT pathway could regulate EAAT2 at multiple levels: by increasing levels of TNF␣, as shown in Fig.…”
Section: Il-mediated Immune/inflammatory Signaling and The Cn/nfatmentioning
confidence: 89%
“…As shown in T cells and cardiomyocytes, inhibition of any of these components may be sufficient to severely limit transcription of target genes, although the activity of each is insufficient to direct transcription on its own (33). Interestingly, EAAT2 levels were recently shown to exhibit down-regulation in response to TNF␣ through a mechanism involving NFB (98). Note then that the CN/NFAT pathway could regulate EAAT2 at multiple levels: by increasing levels of TNF␣, as shown in Fig.…”
Section: Il-mediated Immune/inflammatory Signaling and The Cn/nfatmentioning
confidence: 89%
“…However, others have described a down-regulation of GLT-1 by inflammatory mediators. For instance, a role was assigned to TNF-α during the hypoxia-mediated suppression of GLT-1 in astrocytes [29]. These inconsistencies may originate from the diversity of models, pathologies and culture methods tested (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Similarly to hypoxia, the inflammatory cytokine TNF␣ also reduces EAAT2 expression in astrocytes. 63 It is possible that enhancing the EAAT2 abundance in astrocytes could reduce excitotoxicity in stroke and neurodegenerative diseases. A screen to identify drugs that induce EAAT2 demonstrated that the ␤-lactam antibiotics, especially ceftriaxone (CFX), increase the expression of EAAT2 in organotypic spinal cord slice cultures.…”
Section: Astrocytes Edema and Volume Regulation In Strokementioning
confidence: 99%